Cucurbitacin B induces neurogenesis in PC12 cells and protects memory in APP/PS1 mice. Issue 9 (30th June 2019) - Li, Jing; Sun, Kaiyue; Muroi, Makoto; Gao, Lijuan; Chang, Young‐Tae; Osada, Hiroyuki; Xiang, Lan; Qi, Jianhua
Abstract: Cucurbitacin B (CuB) isolated from Cucumis melo by using a PC12 cell bioassay system exhibited significant nerve growth factor (NGF)‐mimic or NGF‐enhancing activity in PC12 and primary neuron cells. It was also demonstrated pro‐neurogenesis effects in ICR and APP/PS1 mice and improved memory deficit of APP/PS1 mice. Its possible mechanism includes significant induction of the phosphorylation of glucocorticoid receptor (GR), protein kinase C (PKC), phospholipase C (PLC) and inhibition of cofilin. ChemProteoBase profiling, binding assay and cellular thermal shift assay (CETSA) were used to determine the target protein. Results revealed that CuB could affect actin dynamics as an actin inhibitor but did not bind with GR. The protein level of cofilin in PC12 cells after treating 0.3 μM and different temperatures was significantly higher than that of control group. Other neurotrophic signalling pathways, such as TrkA/TrkB, were analysed with specific inhibitors and Western blot. The inhibitors of TrkA, PLC, PKC, Ras, Raf and ERK1/2 significantly decreased the percentage of PC12 cells with neurite outgrowth and shortened the length of neurite outgrowth induced by CuB. CuB significantly induced the phosphorylation of TrkA, ERK and CREB. The phosphorylation of these proteins was obviously decreased by their specific inhibitors. These results suggest that cofilin is a candidate target protein of CuB in PC12 cells and that the GR/PLC/PKC and TrkA/Ras/Raf/ERK signalling pathways play important roles in the neuroprotective effect of CuB.